1842 Effect of Neuronal Expression of Hent1 and Caffeine on Cerebral Blood Flow and Cortical Stroke in Mice. (October 2012) - Soylu, H; Zhang, D; Buist, R; Martin, M; Albensi, BC; Parkinson, FE
Abstract : Background: Adenosine has neuromodulatory effects in animal stroke models. We previously showed that human equilibrative nucleoside transporter 1 (hENT1) over expression decreases extracellular adenosine action. Caffeine is adenosine receptor antagonist. Objective: To compare the effect of ENT1 over expression on cerebral blood flow (CBF) and subsequent ischemic damage in hENT1 transgenic (Tg) and wild type (Wt) mice following intra-cortical injection of endothelin-1 (ET-1) and giving intraperitoneal (IP) caffeine prior to the ischemic stroke event. Design/methods: 8–10 week old CD1 and Tg mice were stratified as Group A (n = 25), received unilateral single cortical injection of ET-1 and Group B (n=20) received 25 mg/kg IP caffeine prior to ET-1 injection. CBF was measured at 4 hours and 48 hours and stroke size was measured at 48 hours by MRI. Results: At 4 hours ipsilateral CBF decreased significantly (p<0.01), which was more prominent in Tg mice and was still evident at 48 hours. ET-1 produced greater infarct size in Tg (9±1.1 mm 3 ) than Wt (5.4±0.8 mm 3 ) mice without given caffeine. However, there was no difference in infarct size between Tg (6.2±1 mm 3 ) and Wt (6.7±1 mm 3 ) mice in caffeine injected group. Conclusions: This study showed that hENT1 over expression is associated with increased cerebral infarct size. This genotype difference was not observed in mice received caffeine. These data are consistent with our previous findings that hENT1 Tg mice have reduced basal adenosine levels and reduced ischemia evoked increases in adenosine as compared to Wt mice.